Determinan Pengungkapan Emisi Karbon dan Pengaruhnya Terhadap Kinerja Keuangan - Rindy Dwi Ladista; Lindrianasari Lindrianasari; Usep Syaipudin (Owner : Riset dan Jurnal Akuntansi, 2023)
This study examines to provide empirical evidence to the determinants of carbon emission disclosure, namely carbon performance, green innovation (green products and processes), environmental costs, and the proportion of female directors, and the effect of carbon emission disclosure on financial performance. The novelty of this research is to propose novelty in calculating carbon performance, by the comparison of carbon producing assets and total carbon emissions and using green product innovation as an independent variable. The population of this study are companies listed on the IDX from 2019-2021, published annual report and sustainability report, disclose emission total and environmental cost. Data is processed using panel data regression analysis, random effect model. Based on the results of the study it was concluded that carbon performance and the proportion of female directors proved to have a positive and significant effect on carbon emission disclosure. While the green product innovation, green process innovation, and environmental costs are not proven to have a significant effect on carbon emission disclosure. In this study, carbon emission disclosure is not proven to have a significant effect on profitability and firm value. This study also found that there are no regulities about total emission measurement and environmental cost.